2023
DOI: 10.5853/jos.2023.00752
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy for Large Ischemic Strokes: A Living Systematic Review and Meta-Analysis of Randomized Trials

Abstract: Background and Purpose New studies have shown that endovascular thrombectomy (EVT) is safe and effective for acute ischemic stroke (AIS) patients with large ischemic areas. The aim of our study is to conduct a living systematic review and meta-analysis of randomized trials comparing EVT versus medical management only.Methods We searched MEDLINE, Embase, and the Cochrane Library to identify randomized controlled trials (RCTs) comparing EVT versus medical management alone in AIS patients with large ischemic regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Understanding the mechanisms of thrombosis plays a pivotal role in determining the appropriate treatment strategies. Endovascular thrombectomy (EVT) has proven effective in patients with acute stroke due to large vessel occlusion in both the anterior and posterior circulations [ 28 , 29 ]. The successful implementation of EVT in patients with acute ischemic stroke has allowed for the retrieval of fresh thrombi from the cerebral arteries, enabling histopathological analysis and research [ 30 , 31 ].…”
Section: Thrombus Histopathology In Cancer-associated Strokementioning
confidence: 99%
“…Understanding the mechanisms of thrombosis plays a pivotal role in determining the appropriate treatment strategies. Endovascular thrombectomy (EVT) has proven effective in patients with acute stroke due to large vessel occlusion in both the anterior and posterior circulations [ 28 , 29 ]. The successful implementation of EVT in patients with acute ischemic stroke has allowed for the retrieval of fresh thrombi from the cerebral arteries, enabling histopathological analysis and research [ 30 , 31 ].…”
Section: Thrombus Histopathology In Cancer-associated Strokementioning
confidence: 99%
“…Endovascular thrombectomy (EVT) has become the standard of care for patients with acute ischemic stroke (AIS) due to large-vessel occlusion (LVO). Several randomized clinical trials (RCTs) and meta-analyses have demonstrated that EVT significantly improves functional outcomes and reduces disability compared with medical management alone in these patients. However, despite high rates of recanalization with EVT, a substantial proportion of patients still have poor functional outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular thrombectomy (EVT) has been established as an effective therapy for acute ischemic stroke (AIS) with large vessel occlusion (LVO) [ 1 , 2 ]. Despite successful recanalization after EVT, a significant number of patients do not achieve functional independence [ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%